2021
DOI: 10.48550/arxiv.2103.01183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In the Realm of the Hubble tension $-$ a Review of Solutions

Eleonora Di Valentino,
Olga Mena,
Supriya Pan
et al.

Abstract: The simplest ΛCDM model provides a good fit to a large span of cosmological data but harbors large areas of phenomenology and ignorance. With the improvement of the number and the accuracy of observations, discrepancies among key cosmological parameters of the model have emerged. The most statistically significant tension is the 4σ to 6σ disagreement between predictions of the Hubble constant, H 0 , made by the early time probes in concert with the "vanilla" ΛCDM Cosmological model, and a number of late time, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
275
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(281 citation statements)
references
References 709 publications
(1,036 reference statements)
4
275
0
2
Order By: Relevance
“…In case of a neutrino mass discovery at KATRIN, a more involved analysis including inversedecays would be necessary to firmly confirm that the decay scenario can reconcile laboratory and cosmological measurements. Additionally, our results show that the tentative exclusion of the inverted mass ordering [42][43][44][45], based solely on the fact that the inverted ordering predicts m ν > 0.1 eV, is highly dependent on the hypothesis that neutrinos are stable on cosmological time-scales. Nonrelativistic decays can still easily reconcile the inverted ordering with cosmological data.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In case of a neutrino mass discovery at KATRIN, a more involved analysis including inversedecays would be necessary to firmly confirm that the decay scenario can reconcile laboratory and cosmological measurements. Additionally, our results show that the tentative exclusion of the inverted mass ordering [42][43][44][45], based solely on the fact that the inverted ordering predicts m ν > 0.1 eV, is highly dependent on the hypothesis that neutrinos are stable on cosmological time-scales. Nonrelativistic decays can still easily reconcile the inverted ordering with cosmological data.…”
Section: Discussionmentioning
confidence: 76%
“…In recent years, a number of studies have attempted to constrain the neutrino mass ordering, showing that under the assumption of stable neutrinos, the inverted ordering is now disfavored by a compilation of cosmological data [42][43][44] as well as from Ly-α observations [45]. However, these arguments are centered on the fact that these analyse leads to a constraint on m ν at odds with the lower bound on the sum of neutrino masses in the case of inverted ordering, m ν 0.1 eV.…”
Section: Parameter Space Of Decaying Neutrinosmentioning
confidence: 99%
“…Allowing 𝑁 eff to be a free parameter may be particularly interesting in the context of the Hubble tension (a potential solution to the problem involves allowing for extra species of neutrinos, i.e. 'dark radiation', (Di Valentino et al 2021), and 𝑁 eff is particularly degenerate with 𝑚 𝜈 ). Furthermore, in the case we would like an independent comparison of constraints on 𝑚 𝜈 between early Universe probes (such as the constraints from the Planck measurements of the CMB) and late Universe probes (such as galaxy surveys), we have demonstrated that peculiar velocities allow this to be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this model suffers from unsolved issues -such as the fine-tuning and the primordial singularity problems, to name a few. As of recently, tensions between cosmological parameter measurements within its framework have been persisting -the most stringent at the moment being the 4.5σ tension between the H 0 measured in the late-and early-time Universe from SNe and CMB, respectively [17,18].…”
Section: Introductionmentioning
confidence: 99%